Discovery of Anticancer Agents from 2-Pyrazoline-Based Compounds - Li, Qing-Shan; Shen, Bang-Nian; Zhang, Zhen; Luo, Shuying; Ruan, Ban-Feng (Current Medicinal Chemistry, 2021)
As nitrogen-containing five-membered heterocyclic structural units, the substituted pyrazole derivatives have a broad spectrum of pharmacological activities, especially 4,5-dihydro-1H-pyrazoles that also commonly known as 2-pyrazolines. Since 2010, considerable studies have been found that the 2-pyrazoline derivatives possess potent anticancer activities. In the present review, it covers the pyrazoline derivatives reported by literature from 2010 till date (2010-2019). This review aims to establish the relationship between the anticancer activities variation and different substituents introduced into a 2-pyrazoline core, which could provide important pharmacophore clues for the discovery of new anticancer agents containing 2-pyrazoline scaffold.
Keywords: 2-pyrazoline